PENGARUH MODEL INKUIRI TERBIMBING TERHADAP KETERAMPILAN PROSES SAINS PADA PEMBELAJARAN IPA DI SD - Hadie, Yamin; Kresnadi, Hery; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze the influence of guided inquiry models on students' science process skills in the learning of Natural Sciences class V State Elementary School 03 Segedong. The research method used is an experimental method of Pre-Experimental Design type One-Group Pretest-Posttest Design. The population in this study were all class V 03 Segedong State Elementary School with a total of 21 students. The sample selection is done by saturated sampling obtained all students of class V into the experimental class. Data collection tool in the form of a test with a number of 40 multiple choice questions. Based on the results of the t test calculations obtained t_count (12.57)> ttable (1.725) with a significant level Î± = 0.05 means there is a significant influence on the application of the guided inquiry model. From the results of the calculation of the effect size (ES), amounting to 1.03 with high criteria. This means that the guided inquiry model has a moderate influence on the science process skills in the learning of Natural Sciences of the fifth grade students of State Elementary School 03 SegedongÂ Keywords: Guided Inquiry, Science Process Skills